Сповідь жертви й інтонація помсти: голод, терор і письмо - Василенко, В.С. (Слово і Час, 2019)
Статтю присвячено дослідженню художнього й автобіографічного досвідів тоталітарних репресій і Голодомору в прозі Ольги Мак. До аналізу залучено художні, мемуарні, публіцистичні твори письменниці, зокрема спогади “З часів єжовщини”, нарис “Столиця голодного жаху”, повість “Каміння під косою”, які розглянуто в контексті художньої й документальної прози повоєнної української діаспори. The paper considers repressions and Holodomor as a kind of literary practice and traumatic experience in the works and biography of the Ukrainian diaspora writer Olha Mak. The analysis covers fiction, memoirs, and journalistic texts, in particular the memoirs “From the Time of Yezhovshchyna”, the essay “Capital of Hungry Horror”, and the story “Stones Under Scythe”, considered in the context of the fiction and documentaries of the postwar Ukrainian diaspora. In this case, the writing appears to be a vital natural resource for recreating the memory, where one’s own individual experience becomes a material, an object for self-refl ection. The process of writing is associated with moral and ethical duty of witnessing the past; it has a powerful therapeutic meaning and protects from immorality integrating individual experience and history into collective, social, cultural, etc. The memoir “From the Time of Yezhovshchyna” by Olha Mack, dealing with the theme of Soviet terror and repressions, is a peculiar form of re-experiencing a personal tragedy associated with the arrest and deportation of the author’s husband. It shows the self-denial of the Soviet human, the wife of the ‘enemy of people’, and records her traumatic experience and memories. The Holodomor theme, elaborated by Olha Mack in various genres and forms, was not only a material, an object of research, but also a part of her personal biography and family history. The Holodomor in the perception of Olha Mack symbolized the threat to social, national (spiritual) life connected with various social, cultural, and mental illnesses; hence, it involves the idea of eliminating Ukraine not only as material and spatial entity, but also as abstract and spiritual one. The story “Stones Under Scythe”, dedicated to the memory of the Holodomor, is considered as a kind of the classical bildungsroman genre’s variation. Its conceptual figures are images-archetypes of the child-victim, the female martyr, the great mother. The Holodomor (both physical and spiritual, which destroys the foundations of national dignity, national solidarity and so on) in the story by Olha Mack is not only the topic, but also a continual metaphor and key motive.